Advances in Mechanical Design Proceedings of the 2017 International Conference on Mechanical Design (ICMD2017) - Tan, Jianrong; Gao, Feng; Xiang, Changle (Mechanisms and Machine Science, 2018)
Focusing on innovation, these proceedings present recent advances in the field of mechanical design in China and offer researchers, scholars and scientists an international platform to present their research findings and exchange their ideas. In the context of the "Made in China 2025" development strategy, one central aspect of the ICMD2017 was Innovative Design Pushes "Made in China 2025." The book highlights research hotspots in mechanical design, such as design methodology, green design, robotics and mechanics, and reliability design, while also combining industrial design and mechanical design.